Contemporary Sex-Based Differences by Age in Presenting Characteristics, Use of an Early Invasive Strategy, and Inhospital Mortality in Patients With Non–ST-Segment–Elevation Myocardial Infarction in the United States. (January 2018) - Gupta, Tanush; Kolte, Dhaval; Khera, Sahil; Agarwal, Nayan; Villablanca, Pedro A.; Goel, Kashish; Patel, Kavisha; Aronow, Wilbert S.; Wiley, Jose; Bortnick, Anna E.; Aronow, Herbert D.; Abbott, J. Dawn; et al.
Abstract : Background—: Prior studies have reported higher inhospital mortality in women versus men with non–ST-segment–elevation myocardial infarction. Whether this is because of worse baseline risk profile compared with men or sex-based disparities in treatment is not completely understood. Methods and Results—: We queried the 2003 to 2014 National Inpatient Sample databases to identify all hospitalizations in patients aged ≥18 years with the principal diagnosis of non–ST-segment–elevation myocardial infarction. Complex samples multivariable logistic regression models were used to examine sex differences in use of an early invasive strategy and inhospital mortality. Of 4 765 739 patients with non–ST-segment–elevation myocardial infarction, 2 026 285 (42.5%) were women. Women were on average 6 years older than men and had a higher comorbidity burden. Women were less likely to be treated with an early invasive strategy (29.4% versus 39.2%; adjusted odds ratio, 0.92; 95% confidence interval, 0.91–0.94). Women had higher crude inhospital mortality than men (4.7% versus 3.9%; unadjusted odds ratio, 1.22; 95% confidence interval, 1.20–1.25). After adjustment for age (adjusted odds ratio, 0.96; 95% confidence interval, 0.94–0.98) and additionally for comorbidities, other demographics, and hospital characteristics, women had 10% lower odds of inhospital mortality (adjusted odds ratio, 0.90; 95% confidence interval, 0.89–0.92). Further adjustment for differences in the use of an early invasive strategy did not change the association between female sex and lower risk-adjusted inhospital mortality. Conclusions—: Although women were less likely to be treated with an early invasive strategy compared with men, the lower use of an early invasive strategy was not responsible for the higher crude inhospital mortality in women, which could be entirely explained by older age and higher comorbidity burden. Abstract : Supplemental Digital Content is available in the text.